2014
DOI: 10.4269/ajtmh.13-0384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Accuracy of a Typhoid IgM Flow Assay for the Diagnosis of Typhoid Fever in Cambodian Children Using a Bayesian Latent Class Model Assuming an Imperfect Gold Standard

Abstract: Rapid diagnostic tests are needed for typhoid fever (TF) diagnosis in febrile children in endemic areas. Five hundred children admitted to the hospital in Cambodia between 2009 and 2010 with documented fever (≥ 38°C) were investigated using blood cultures (BCs), Salmonella Typhi/Paratyphi A real-time polymerase chain reactions (PCRs), and a Typhoid immunoglobulin M flow assay (IgMFA). Test performance was determined by conventional methods and Bayesian latent class modeling. There were 32 cases of TF (10 BC- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 26 publications
2
55
1
2
Order By: Relevance
“…5,8 Positivity rate of blood culture was considered low. In contrast to a previous study which stated that the best period for blood culture is day <7 of disease, [14][15][16] the highest rate was noted on day 7. Low positivity rates of blood culture, which was also reported in a previous study, may as well be results from prior antibiotic use.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…5,8 Positivity rate of blood culture was considered low. In contrast to a previous study which stated that the best period for blood culture is day <7 of disease, [14][15][16] the highest rate was noted on day 7. Low positivity rates of blood culture, which was also reported in a previous study, may as well be results from prior antibiotic use.…”
Section: Discussioncontrasting
confidence: 51%
“…High sensitivity and low specificity of the test were also reported in the childrenpopulated study performed by Narayanappa, et al 11 This retrospective study was a hospitalbased study where most patients had previously visited the primary health care. Children with 1-14 days of fever were included because the best period of blood culture are the first few days of disease [14][15][16] and the best period of IgM anti S. typhi serologic test is the second week of disease. 5,8 The facts that antibiotics were widely used prior to the admission of patients could make the number of study subjects even lower and impossible to conduct this study; thus, children with prior antibiotic use were not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity among patients with other conditions has usually been 100%. Several studies have reported patients with clinically suspected typhoid who are PCR positive and blood culture negative (266,272). The absence of a perfect reference standard makes interpretation of these results challenging.…”
Section: Molecular Assaysmentioning
confidence: 99%
“…The sensitivity of PCR without enrichment in blood-culture positive cases has exceeded 90% in some studies (271,273,(278)(279)(280)(281)(282)(283)(284)(285)(286), although other studies have reported much lower sensitivities more consistent with the number of bacteria in the blood (266,272,287). Bone marrow aspirates were examined in one study, with 100% sensitivity (287), and positive results have also been found in urine samples (288).…”
Section: Molecular Assaysmentioning
confidence: 99%
See 1 more Smart Citation